MUCOADHESION AND INNOVATION: INSIGHTS AND CHALLENGES IN THE EXPERIMENTAL EVALUATION OF MUCOADHESIVE SYSTEMS - Tavares, Luciana Cláudia Diniz; de Oliveira, Amanda Marota; Apolônio, Ana Carolina Morais; Moraes, Matheus Fernandes Lasneau; de Oliveira, Mariana Simões; Marcomini, Raphael Fortes; Gomes, Taleessa Vieira; Caetano, Tharcísio Amadeu Tomaz; Clemente, Vitória Batista (Seven Editora, 2026)
Mucoadhesion has become a central strategy in the development of drug delivery systems, especially in applications that require prolonged retention on mucosal surfaces and greater local therapeutic efficiency. However, the advancement of this field has not been accompanied by equal robustness in the experimental approaches used for its evaluation. This chapter critically analyzes the main obstacles associated with the characterization of mucoadhesive systems, articulating theoretical, methodological, instrumental, and structural dimensions that condition contemporary scientific practice. It is evident that the heterogeneity of protocols, the lack of standardization, and the dependence on adapted equipment compromise the comparability between studies and weaken the construction of an integrated body of knowledge. The centrality of the contact interface is particularly highlighted, especially regarding the inadequacy of the probes used, whose variability directly influences the results obtained. In parallel, limitations related to access to infrastructure, operational costs, technical training, and regional inequalities increase the complexity of the experimental scenario, impacting reproducibility and the pace of scientific production. The convergence of these factors points to the exhaustion of the current evaluation model, sustained by incremental adaptations and the absence of dedicated technological solutions. Given this scenario, a structural reconfiguration of the field is necessary, guided by the development of specific instrumentation, the incorporation of digital technologies, and the construction of shared methodological references. It is concluded that overcoming current limitations requires not only technical advances but also a paradigmatic shift in the way mucoadhesion assays are conceived, executed, and interpreted—an indispensable condition for consolidating more consistent, comparable, and clinically relevant results.